Digital Literacy Education as an Effort to Build a Generation of Technology-Savvy and Economically Independent Village Teenagers - Miswar, Edy; Siregar, M. Ridha; Ramadhan, Fakhri; Nisva, Raisa Ullya; Zikran, Ghrina; Humaira, Radhia; Maulana, Rizki; Saddaq, Mizan (Jurnal Pengabdian Bakti Akademisi, 2024)
The community service activity themed "Digital Literacy Education as an Effort to Build a Generation of Technology-Savvy and Independent Village Teenagers" aims to improve digital literacy among village teenagers. This activity was carried out in Beurandeh Village, Mesjid Raya District, Aceh Besar Regency, involving 40 teenagers as participants. The program uses a Participatory Action Research (PAR) approach, which is divided into four phases: identification, needs determination, intervention, and evaluation. Each phase was designed to improve adolescents' understanding of digital literacy, including an understanding of digital safety, social media ethics, and productive and safe use of technology. The results showed a significant increase in adolescents' understanding and awareness of the importance of maintaining privacy and avoiding the spread of hoaxes, with an 85% increase in understanding. In addition, village officials also reported an increase in their ability to discuss digital literacy topics with teenagers, demonstrating the positive effects of the socialization. Although challenges such as lack of resources and limited parental understanding still exist, this activity is expected to have a long-term impact in building a generation of tech-savvy and independent teenagers, who are better prepared to face digital risks in the future.